PENGARUH PENGALAMAN AUDIT, TEKANAN KETAATAN DAN INDEPENDENSI TERHADAP AUDIT JUDGMENT (Studi Pada Kantor Akuntan Publik DKI JAKARTA) - Fitri Hani Fatunnisa (2020)
This study aims to find empirical evidence and analyze the significant influence of audit experience, compliance pressure and independence of Audit Judgment. The sample used in this study were senior auditors, partners and managers working for public accounting firms in Jakarta which were listed in the Public Accountants Office Directory published by the Indonesian Institute of Certified Public Accountants (IAPI) in 2019. Sampling was done randomly and obtained as many as 90 respondents. The analysis technique used in this study is PLS program with a significant level of 5%. The results of this study were obtained as follows: audit experience and independence significantly influence Audit Judgments, whereas compliance pressure does not significantly influence Audit Judgments.